Detection of Transovarial Transmission on Aedes sp. in Gombong Kebumen Central Java - Siwi Pramatama Mars Wijayanti; Devi Octaviana; Arnika Dwi Asti (ASPIRATOR - Journal of Vector-borne Disease Studies, 2019)
Abstract. Gombong Subdistrict is one of dengue-endemic area in Kebumen Regency, Central Java. The high number of dengue cases in this area raises the question of whether there has been transovarial transmission occured from the Aedes sp. to their eggs. Transovarial transmission could be dangerous because the next generation of mosquitoes can directly become competent vectors as transmitters of the dengue virus (DENV). The purpose of this study is to detect dengue virus transovarial transmission in Aedes sp. in Gombong Subdistrict. This is a descriptive research in Gombong, Semanding, and Kali Tengah villages, Gombong Sub District. A total of 300 houses, 100 houses from each village were selected in this study. There were 600 Oviposition traps (ovitraps) were installed both inside and outside of houses for 6 days. Ovitraps were calculated by its Ovitrap Index (OI). Detection of transovarial transmission was carried by rearing field mosquitoes to Filial 1 then identified by RT-PCR assay. This study showed that OI in the three villages was higher in outdoor compared to indoor positions. All tested samples were negative DENV, indicated that there were no transovarial transmission occured at the study sites. Transmission in these study areas might still through horizontal mechanism transmission by mosquito bites. Although there is no transovarial transmission, awareness of dengue transmission must be continued by eradicating of mosquito nests such as 3M plus activities on a regular basis